THE INFLUENCE OF ADVERTISEMENT, PERCEIVED PRICE, AND BRAND IMAGE ON CONSUMER BUYING DECISION TO ASUS MOBILE PHONE - Ruslim, Archi C.; Tumewu, Ferdinand J. (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2015)
Buying decision is the stage in which consumers make the decision or take an action whether to purchase a certain product or not. The purpose of this research is to analyze the simultaneous and partial effect of Advertising, Perceived Price and Brand Images on Consumer Buying Decision. The populations of this research are people who use ASUS smartphone with the sample size as many as 40 respondents. This research uses quantitative analyze by questionnaires and the Multiple Regression Analysis. The result shows that Advertising, Perceived Price and Brand Image have significant effect on consumer buying decision, both simultaneously and partially effect. ASUS mobile phone management should pay more attention to Advertisement that is made and the Price of product so that consumers will still be interested buying the mobile phone. Keywords: advertising, perceived price, brand image, consumer buying decision